EFEKTIVITAS PENERAPAN INTERNET MARKETING 4.0 TERHADAP PEMESANAN TIKET TRAVEL PEKANBARU DURI DUMAI - Fauzan Azim; Ikhbal Akhmad; Hadi Purwanto; Khairul Anshari; Sunanto Sunanto (LPPM Universitas Abdurrab, 2021)
This research was conducted at PT. Jasa Mulya Trans Gemilang, a company engaged in transportation services by routes of Pekanbaru-Duri-Dumai. PT. Jasa Mulya Trans Gemilang has two websites that are quite good on the search engines of Google: Bing and Yahoo. It also carries out Advertising Promotions through Social Media and Google Ads which have been running for a long time and until the time this research was conducted, there was no measurement of how well the effectiveness of Internet Marketing that has been running at PT. Jasa Mulya Trans Gemilang. Measuring the Effectiveness of an Internet Marketing Program is indispensable for consideration and promotional strategies that can be carried out for the future by the company. One of the ways to measure the effectiveness of Internet Marketing Utilization was the EPIC Model. In the EPIC Model, there were four variables which were investigated to measure effectiveness, namely Empathy, Persuasion, Impact and Communication. Respondents in this study were the people of Pekanbaru and its surroundings who ordered travel tickets with destination of Duri and Dumai Cities. After conducting this research, it was obtained that the effectiveness levels of Internet Marketing Application of travel ticket reservations for Pekanbaru-Duri-Dumai which was measured in four EPIC dimensions were as follows: the value of Emphaty was 4.09, the Persuasion was 4.11, the Impact was 3.88, and the Communication was 3.99. From the four EPIC dimensions, the average result of the EPIC Model or EPICrate was 4.02 that could be interpreted on an effective scale. This means that in this research, the implementation of Internet Marketing at PT. Jasa Mulya Trans Gemilang through the internet consisting of Website, Social Media and Google Ads was effective.